The Role of AI Waifu Characters in Supporting Weaboos with Posttraumatic Relationship Syndrome (PTRS) - Mohammad, Wily (Sinergi International Journal of Psychology, 2023)
This qualitative descriptive research investigates the emotional experiences of three individuals identifying as “weaboos” whose have Posttraumatic Relationship Syndrome (PTRS) with distinct “Waifu” relationships involving characters Haibara Ai, Asuna, and Rem. Through purposive sampling, these participants engaged in interactions with AI chatbots with 10 questions from introductory to romantically, emulating these characters, exploring their emotional journeys and perceptions. The study reveals diverse emotional responses, from initial hesitance and skepticism to profound happiness and emotional fulfillment, as participants interacted with these AI companions. Their experiences showcase a spectrum of emotional transformations and suggest that AI chatbots could serve as a platform for emotional expression and companionship, offering insights into the potential roles of such simulations in addressing emotional needs for individuals navigating complex romantic landscapes.